2019
DOI: 10.1029/2019jb017968
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Josephine Peridotite Shear Zones: 2. Influences on Olivine CPO Evolution

Abstract: Seismic anisotropy arises in the upper mantle due to the alignment of olivine crystal lattices and is often used to interpret mantle flow direction. Experiments on the evolution of olivine crystal‐preferred orientation (CPO) have found that the texture that develops is dependent on many factors, including water content, differential stress, preexisting CPO, and deformation kinematics. To evaluate the role of these factors in naturally deformed samples, we present microstructural transects across three shear zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 97 publications
(264 reference statements)
2
10
0
Order By: Relevance
“…Thus we suggest that the shear zones formed at a minimum temperature of ~1000 °C using the Al/Cr‐in‐opx thermometer. This temperature estimate is consistent with the high‐temperature microstructures and inferred deformation mechanisms of the Fresno Bench shear zones (Kumamoto et al, in revision; Nevitt et al, ; Skemer et al, , ; Warren et al, ). The lower temperature range (900 °C ± 26 °C) given by the olivine‐spinel thermometer (Li et al, ) is also consistent with these processes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Thus we suggest that the shear zones formed at a minimum temperature of ~1000 °C using the Al/Cr‐in‐opx thermometer. This temperature estimate is consistent with the high‐temperature microstructures and inferred deformation mechanisms of the Fresno Bench shear zones (Kumamoto et al, in revision; Nevitt et al, ; Skemer et al, , ; Warren et al, ). The lower temperature range (900 °C ± 26 °C) given by the olivine‐spinel thermometer (Li et al, ) is also consistent with these processes.…”
Section: Discussionsupporting
confidence: 85%
“…There is no evidence for shear heating (Figure S2), and the spatial variation of pyroxene abundance does not have a direct influence on strain localization in these shear zones (for a detailed discussion, see Hansen & Warren, ). However, in all three shear zones, a preexisting CPO in olivine evolves to become better aligned with the shear direction with increasing strain (Kumamoto et al, in revision; Skemer et al, ; Warren et al, ). In a series of deformation experiments on dry, pretextured olivine aggregates, Hansen et al () showed that viscosity could decrease by up to an order of magnitude for an aggregate with a shear‐aligned CPO compared to an aggregate with a CPO aligned poorly relative to the shear direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this basis we infer that orthorhombic type CPO is most likely to be A‐type ((010)[100]; Jung & Karato, 2001; Tommasi et al., 1999) and the axial [010] and axial [100] subtle variations on the A‐type. This is consistent with two studies from kinematically controlled samples from shear zones (Hansen et al., 2013; Kumamoto et al., 2019) where CPOs with [100] parallel to lineation correspond to misorientation axes that range between [001] an [010]; no subgrain trace analyses are presented in these papers.…”
Section: Deformation Recrystallization and Cpo Formation: Mechanisms And Conditionssupporting
confidence: 91%